Food insecurity is associated with magnetic resonance–determined nonalcoholic fatty liver and liver fibrosis in low-income, middle-aged adults with and without HIV. Issue 3 (29th January 2021) - Tamargo, Javier A; Sherman, Kenneth E; Campa, Adriana; Martinez, Sabrina S; Li, Tan; Hernandez, Jacqueline; Teeman, Colby; Mandler, Raul N; Chen, Jun; Ehman, Richard L; Baum, Marianna K
ABSTRACT: Background: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease in the United States. Food-insecure individuals often depend on low-cost, energy-dense but nutritionally poor foods, resulting in obesity and chronic diseases related to NAFLD. Objectives: To determine whether food insecurity is associated with NAFLD in a cohort of HIV and hepatitis C virus (HCV) infected and uninfected adults. Methods: We conducted a cross-sectional analysis of low-income, middle-aged adults from the Miami Adult Studies on HIV (MASH) cohort without a history of excessive alcohol consumption. Food security was assessed with the USDA's Household Food Security Survey. MRIs were used to assess liver steatosis and fibrosis. Metabolic parameters were assessed from fasting blood, anthropometrics, and vitals. Results: Of the total 603 participants, 32.0% reported food insecurity. The prevalences of NAFLD, fibrosis, and advanced fibrosis were 16.1%, 15.1%, and 4.6%, respectively. For every 5 kg/m 2 increase in BMI, the odds of NAFLD increased by a factor of 3.83 (95% CI, 2.37–6.19) in food-insecure participants compared to 1.32 (95% CI, 1.04–1.67) in food-secure participants. Food insecurity was associated with increased odds for any liver fibrosis (OR, 1.65; 95% CI, 1.01–2.72) and advanced liver fibrosis (OR, 2.82; 95% CI, 1.22–6.54), adjusted for confounders. HIV and HCV infections were associated with increased risks for fibrosis, but the relationship between food insecurity and liver fibrosis did not differ between infected and uninfected participants. Conclusions: Among low-income, middle-aged adults, food insecurity exacerbated the risk for NAFLD associated with a higher BMI and independently increased the risk for advanced liver fibrosis. People who experience food insecurity, particularly those vulnerable to chronic diseases and viral infections, may be at increased risk for liver-related morbidity and mortality. Improving access to adequate nutrition and preventing obesity among low-income groups may lessen the growing burden of NAFLD and other chronic diseases.